Spatial ARMA model for wind speed data - Paulionienė, Laura (Lietuvos matematikos rinkinys, 2012)
Spatial time series model for wind speed data is proposed. Based on few similar papers, first at each location univariate time series model, containing seasonal component and higher order autoregressive component is fitted. After eliminating time dependence in time series, empirical semivariogram based on time independent residuals is fitted and spatial weights for new location are calculated.